2015
DOI: 10.1590/0102-33062014abb3509
|View full text |Cite
|
Sign up to set email alerts
|

Structure and floristic similarities of upper montane forests in Serra Fina mountain range, southeastern Brazil

Abstract: The upper montane forests in the southern and southeastern regions of Brazil have an unusual and discontinuous geographic distribution at the top of the Atlantic coastal mountain ranges. To describe the floristic composition and structure of the Atlantic Forest near its upper altitudinal limit in southeastern Brazil, 30 plots with 10  10 m were installed in three forest sites between 2,200 and 2,300 m.a.s.l. at Serra Fina. The floristic composition and phytosociological structure of this forest were compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 49 publications
0
19
0
3
Order By: Relevance
“…This pattern is also found in the Southeasten Region, in the MNF of São Paulo state (Pereira Silva et al 2007;Polisel et al 2014). In the cloud broadleaved dwarf-forest of Serra Fina, Meireles & Shepherd (2015) highlighted the importance of this family in addition to other studies conducted in the upper highlands of the Atlantic Domain, where the abundance of Asteraceae species is associated with high elevation (Brade 1956;Falkenberg 2003;Meireles et al 2014).…”
Section: Floristic Compositionmentioning
confidence: 55%
See 2 more Smart Citations
“…This pattern is also found in the Southeasten Region, in the MNF of São Paulo state (Pereira Silva et al 2007;Polisel et al 2014). In the cloud broadleaved dwarf-forest of Serra Fina, Meireles & Shepherd (2015) highlighted the importance of this family in addition to other studies conducted in the upper highlands of the Atlantic Domain, where the abundance of Asteraceae species is associated with high elevation (Brade 1956;Falkenberg 2003;Meireles et al 2014).…”
Section: Floristic Compositionmentioning
confidence: 55%
“…Baccharis is one of the richest genera in the MNF of the PESP. Meireles & Shepherd (2015) and Falkenberg (2003) also found this genus among the richest in forests of Serra Fina (in the triple border of Minas Gerais, Rio de Janeiro and São Paulo state) and Aparados da Serra (between Santa Catarina and Rio Grande do Sul), respectively. The Andes and mountainous regions of Southeastern Brazil are the main centers of diversity for Baccharis (Müller 2006).…”
Section: Floristic Compositionmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, our results suggest that rare AF subtypes, such as cloud, swamp, Caxetal and Mussununga forests, are still underrepresented within the AF. In addition to their rarity, cloud and Mussununga forests may also shelter considerable levels of plant endemisms (Thomas et al 1998;Meireles and Shepherd 2015). Therefore, making wise decisions to conserve the AF will depend not only on obtaining more quality information but also on more homogeneous coverage of these rarer or more threatened AF formations.…”
Section: Discussionmentioning
confidence: 99%
“…In South America, the most important orographic features of the Atlantic coast are the mountains of the Serra do Mar and the Serra da Mantiqueira (Almeida & Carneiro, 1998), which have a strong influence on the climatic conditions in the South and Southeast of Brazil. Previous studies reported floristic similarities between these highlands (Bertoncello et al, 2011;Meireles & Shepherd, 2015), high tree species richness (Pompeu et al, 2014), and a high proportion of endemic species (Meireles et al, 2014). The mountains harbor part of the Brazilian Atlantic Forest (BAF) (Oliveira-Filho & Fontes, 2000), one of the 36 currently recognized global biodiversity hotspots with an exceptionally high number of endemic species (about 8000 are vascular plants species and almost 600 are vertebrate species, Myers et al, 2000) and a high level of habitat loss (Myers et al, 2000;Conservation International, 2018).…”
Section: Introductionmentioning
confidence: 89%